Strategi Pemasaran PT. Annur Maknah Wisata Tour & Travel Kantor Cabang Musi Banyuasin Dalam Meningkatkan Minat Masyarakat Terhadap Layanan Haji Dan Umrah - Muhammad Luthfi Bahrul Ulum (STAIN MAJENE, 2025)
This study aims to analyze the marketing strategies implemented by PT. Annur Maknah Wisata Tour & Travel in increasing public interest in Hajj and Umrah services. This research employs a qualitative descriptive approach using data collection techniques such as in-depth interviews, direct observations, and documentation. The informants consist of company management, marketing staff, customers, and prospective pilgrims. The findings reveal that PT. Annur Maknah Wisata’s marketing strategy focuses on three main aspects: digital promotion through social media, personalized and transparent customer service, and strengthening the company’s reputation and credibility as a professional and trustworthy travel agency. These strategies effectively enhance public interest and trust, as indicated by the annual increase in the number of pilgrims and customer loyalty. Supporting factors include competent human resources and extensive partnership networks, while the main challenges involve intense competition among travel agencies and economic fluctuations. The limitation of this study lies in its focus on a single company, which restricts the generalizability of the findings. The novelty of this research lies in its exploration of Islamic marketing practices grounded in spiritual values and worship-oriented service, offering insights for the development of marketing strategies within the religious travel service sector in Indonesia.